Lexical and morphological features of the work "Khosrov and Shyrin" by Gyutb (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The paper works Gyutba «Khosrow and Shirin» is a comparison of features of the language, as well as investigate the lexical-semantic, lexical-morphological structure of literary works proizvedeniya.Pervoe Gyutba «Khosrow and Shirin», is the oldest text written in Kyzylorda, is the firstborn 21 mesnevi «Khosrow and Shirin» written in Turkish literature. Faced with the Turkish words 80 to 100 in mesnevi Nizami Gyutba this work is in fact a rich vocabulary.
Keywords: Gyutb; «Khosrow and Shirin»; vocabulary; morphological properties; the poem